Perbandingan Penerapan Model Pembelajaran Creative Problem Solving (CPS) dengan Model Pembelajaran Problem Solving terhadap Kemampuan Berpikir Kritis Peserta Didik - Nurjannah; Suharti; Nursalam (Alauddin Journal of Mathematics Education, 2025)
Critical thinking ability is one of the important competencies that must be developed in mathematics learning, especially in linear programming material that requires logical analysis and decision making. This research is important to conduct because the critical thinking ability of students in schools still tends to be low and requires more effective learning strategies to improve it. This study aims to compare the effectiveness of the Creative Problem Solving (CPS) and Problem Solving learning models in improving students' critical thinking abilities. The study used a quantitative approach with a posttest only control group design in a quasi-experimental experiment. The study population was all grade XI students of SMAN 8 Takalar, with a sample of 62 students divided into two experimental classes, each with 31 students. The research instrument was a critical thinking ability test. The results of the t-test showed a significant difference between the two groups (t count = 6.061 > t table = 2.01). Thus, it can be concluded that there is a difference in the critical thinking ability of students taught using the Creative Problem Solving (CPS) model and the Problem Solving model. Based on the average posttest score, students in the CPS class achieved higher results than those in the class using the Problem Solving model, thus it can be stated that the CPS model is more effective in improving students' mathematical critical thinking skills. The implication of this finding is that teachers are advised to apply the CPS model as an alternative learning strategy to improve the quality of students' understanding and critical thinking skills. This study contributes by providing empirical evidence regarding the advantages of CPS in mathematics learning, especially in the context of linear programming material.